Whole-genome sequencing and genetic diversity of severe fever with thrombocytopenia syndrome virus using multiplex PCR-based nanopore sequencing, Republic of Korea. - Jingyeong Lee; Kyungmin Park; Jongwoo Kim; Seung-Ho Lee; Geum-Young Lee; Seungchan Cho; Heung-Chul Kim; Terry A Klein; Jeong-Ah Kim; Jeewan Choi; Juwan Park; Dong-Hyun Song; et al. (Public Library of Science (PLoS), 2022)
Background Whole-genome sequencing plays a critical role in the genomic epidemiology intended to improve understanding the spread of emerging viruses. Dabie bandavirus, causing severe fever with thrombocytopenia syndrome (SFTS), is a zoonotic tick-borne virus that poses a significant public health threat. We aimed to evaluate a novel amplicon-based nanopore sequencing tool to obtain whole-genome sequences of Dabie bandavirus, also known as SFTS virus (SFTSV), and investigate the molecular prevalence in wild ticks, Republic of Korea (ROK). Principal findings A total of 6,593 ticks were collected from Gyeonggi and Gangwon Provinces, ROK in 2019 and 2020. Quantitative polymerase chain reaction revealed the presence of SFSTV RNA in three Haemaphysalis longicornis ticks. Two SFTSV strains were isolated from H. longicornis captured from Pocheon and Cheorwon. Multiplex polymerase chain reaction-based nanopore sequencing provided nearly full-length tripartite genome sequences of SFTSV within one hour running. Phylogenetic and reassortment analyses were performed to infer evolutionary relationships among SFTSVs. Phylogenetic analysis grouped SFTSV Hl19-31-4 and Hl19-31-13 from Pocheon with sub-genotype B-1 in all segments. SFTSV Hl20-8 was found to be a genomic organization compatible with B-1 (for L segment) and B-2 (for M and S segments) sub-genotypes, indicating a natural reassortment between sub-genotypes. Conclusion/significance Amplicon-based next-generation sequencing is a robust tool for whole-genome sequencing of SFTSV using the nanopore platform. The molecular prevalence and geographical distribution of SFTSV enhanced the phylogeographic map at high resolution for sophisticated prevention of emerging SFTS in endemic areas. Our findings provide important insights into the rapid whole-genome sequencing and genetic diversity for the genome-based diagnosis of SFTSV in the endemic outbreak.